1967
DOI: 10.1071/zo9670715
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the ectoparasites of seals and penguins. III. The distribution of the tick Ixodes uriae White and the flea Parapsyllus magellanicus heardi de Meillon on Macquarie Island

Abstract: On Macquarie I. it rains daily and abundantly; whether the habitat is flooded or not determines whether the tick Ixodes uriae and the flea Pavapsyllus magellanicus heardi can survive and breed. The principal hosts of these ectoparasites are penguins; the degree of infestation of the four species of penguins that breed on Macquarie I. differs because of differences in their breeding and moulting behaviour. Royal penguins, Eudyptes chrysolophus schlegeli, form large colonies which are surrounded by tussock, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 0 publications
4
37
0
2
Order By: Relevance
“…Females laid up to 555 eggs, oviposition initiated after 2-8 weeks, depending on temperature. Eggs may hatch in as little as about 60 days (Murray and Vestjens 1967), but may remain viable for more than a year under certain conditions . Although the entire life cycle can be completed in 407 days under laboratory conditions, Flint and Kostyrko (1967) and found that in the field, the life cycle required 4-5 years, with all instars being capable of overwintering.…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Females laid up to 555 eggs, oviposition initiated after 2-8 weeks, depending on temperature. Eggs may hatch in as little as about 60 days (Murray and Vestjens 1967), but may remain viable for more than a year under certain conditions . Although the entire life cycle can be completed in 407 days under laboratory conditions, Flint and Kostyrko (1967) and found that in the field, the life cycle required 4-5 years, with all instars being capable of overwintering.…”
Section: Natural Historymentioning
confidence: 99%
“…Although the entire life cycle can be completed in 407 days under laboratory conditions, Flint and Kostyrko (1967) and found that in the field, the life cycle required 4-5 years, with all instars being capable of overwintering. Ixodes uriae can be abundant and obvious on sea birds, especially on chicks (see photos in Murray and Vestjens 1967;Bergström et al 1999a). This species has been shown to reduce growth rate and prolong time to fledging for Cassin's auklet (Ptychoramphus aleuticus (Pallas)) nestlings in British Columbia (Morbey 1996).…”
Section: Natural Historymentioning
confidence: 99%
“…Aptenodytes patagonicus, unspecified site of infection, New Zealand (Dumbleton 1953;Bishop and Heath 1998;Dietrich et al 2010) Eudyptes robustus, unspecified site of infection, New Zealand (Heath 2010;Dietrich et al 2010) Eudyptula minor, unspecified site of infection, New Zealand (Bishop and Heath 1998;Dietrich et al 2010) Megadyptes antipodes, unspecified site of infection, New Zealand (Bishop and Heath 1998;Dietrich et al 2010) Ixodes eudyptidis Maskell, 1885 Eudyptes pachyrhynchus, unspecified site of infection, New Zealand (Dumbleton 1953;Bishop and Heath 1998;Dietrich et al 2010) Eudyptula minor, unspecified site of infection, Australia (Murray et al 1991) Megadyptes antipodes, unspecified site of infection, New Zealand (Heath 2010 Aptenodytes fosteri, unspecified site of infection, Macquarie Island, Australia (Major et al 2009) Aptenodytes patagonicus, neck and head (adults) and lower parts (larvae), Possession Island, Crozet Archipelago, southern Indian Ocean (Frenot et al 2001;Gauthier-Clerc et al 2003); Macquarie Island, Australia (Major et al 2009); New Zealand (Dumbleton 1953;Bishop and Heath 1998) Eudyptes chrysocome, unspecified site of infection, New Zealand (Bishop and Heath 1998); Macquarie Island, Australia (Major et al 2009) Eudyptes chrysolophus, unspecified site of infection, Subantarctic (Nutall 1984) Eudyptes pachyrhynchus, unspecified site of infection, New Zealand (Dumbleton 1953;Bishop and Heath 1998) Eudyptes robustus, unspecified site of infection, New Zealand (Dumbleton 1961;Murray et al 1991;Bishop and Heath 1998) Eudyptes sclateri, unspecified site of infection, New Zealand (Dumbleton 1953;Bishop and Heath 1998) Eudyptes schlegeli, unspecified site of infection, Macquarie Island, Australia …”
Section: Ixodes Auritulus Groupmentioning
confidence: 99%
“…nom P. magellanicus) ;Smit 1987), îles Kerguelen (Smit, 1957), Archipel Crozet (groupe oriental) : île de la Possession (Beaucournu et Rodhain, 1991), île Marion (Smit, 1987). Par contre les citations de ce taxon concernant l'île Macquarie (De Meillon, 1952;Murray et Vestjens, 1967) sont à rapporter à P. m. magellanicus Jordan, 1938. Spécificité : Trois taxa du sous-groupe magellanicus sont liés aux oiseaux terrestres : Passeriformes (Turdidés, Prunellidés, ...) et, peut-être, Gruiformes (Rallidés), les 3 autres aux oiseaux marins : c'est évidemment le cas de P. heardi.…”
Section: Larus Dominicanus IIIunclassified
“…Dans un travail, où la puce désignée comme P. m. heardi est en fait P. m. magellanicus, Murray et Vestjens (1967) à l'île Macquarie étudient sa biologie aux dépens d'Eudyptes chrysocome. Ils notent que seuls les nids abrités ou a for tiori dans des cavités sont infestés; ceux, avoisinants, éta blis à l'air libre et soumis aux intempéries, sont dépourvus de puces.…”
Section: Larus Dominicanus IIIunclassified